Transbronchial cryobiopsy under real‐time radial mini-probe with a flexible bronchoscope: six case reports - Juan José Cruz-Rueda; Francisco Javier Velasco-Albendea; María Jesús Gil-Belmonte; Fátima Moreno-Sánchez; Beatriz Agredano-Ávila; Andrés López-Pardo (The Egyptian Journal of Bronchology)
Abstract Radial mini-probe has emerged as a valuable tool in the interventionist management of peripheral lung lesions. Its major limitation is the existent time lapse between image location and sample collection, which does not occur in real-time and may interfere with the quality and representativeness of the specimen. We present six cases of patients who underwent a transbronchial cryobiopsy with a radial mini-probe under real-time visualization of the cryoprobe tip using a flexible bronchoscope. This new method enables real-time visualization of the biopsy collection tool once the target lesion is located, allowing the confirmation of its precise location during biopsy taking.